Bandit - Miles, Ellen (New York : Scholastic, 2011)
Bandit is an adorable black and white Shih Tzu with a mask-like marking over his eyes. Lizzie discovers him at a highway rest stop restaurant. He was abandoned by his owers because he needs an operation and they couldn't afford it. Lizzie and her family take Bandit in and begin fundraising for the expensive procedure.
Keywords: Puppies; Shih tzu